Integration of Lean Methodology and Energy Management in Wooden Industry - Phong, Tran Le; Minh, Nguyen Dat (International Journal of Energy Economics and Policy, 2022)
The application of Lean thinking to energy management is the methodology based on the application of the Lean values and the principles of wastes elimination of Lean system. One is then challenging and questioning why a process is using the amount of energy that it does and why it is using energy during non-production hours. One strives to continuously improve and reduce the energy used by implementing improvement ideas. Todays, the pressure of competition in the energy sector is very high. A enterprise that wants to make a difference should continuously run optimization from the production lines. The objective of this study is to measure the impact of Lean tools on energy consumption and energy efficiency improvement. Through a case study, authors point out changes in production and energy efficiency before and after implementing improvement (Kaizen) projects. Besides, this paper illustrate the framework of Lean tools application into energy sector as a guideline for energy efficiency management in industrial enterprises